2017
DOI: 10.1002/2016jc012167
|View full text |Cite
|
Sign up to set email alerts
|

An inverse method to derive surface fluxes from the closure of oceanic heat and water budgets: Application to the north‐western Mediterranean Sea

Abstract: The large amount of data collected during DeWEX, MOOSE, and HyMeX campaigns in the north‐western Mediterranean in 2012–2013 allowed to implement an inverse method to solve the difficult problem of heat and water budget closure. The inverse method is based on the simulation of the observed heat and water budgets, strongly constrained by observations collected during the campaigns and on the deduction of adjusted surface fluxes. The inverse method uses a genetic algorithm that generates 50,000 simulations of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…It has not been particularly developed for strong winds as one can observe in this region in winter and this can introduce some uncertainty on the role of the atmosphere. Thanks to this data set, Caniaux et al () managed to propose an inverse method to estimate during 1 year heat and water fluxes for the whole northwestern Mediterranean basin and at a fine‐scale resolution (i.e., hourly fluxes and 0.04° × 0.04° longitude, latitude) allowing to close the heat and freshwater budgets. The comparison of theses adjusted fluxes with fluxes estimated at the LION buoy from in situ meteo‐oceanic measurements shows a good correlation ( r2=0.96) and provides a validation of the parameterization used for the estimates of the turbulent air‐sea fluxes from the LION buoy (see Caniaux et al's Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…It has not been particularly developed for strong winds as one can observe in this region in winter and this can introduce some uncertainty on the role of the atmosphere. Thanks to this data set, Caniaux et al () managed to propose an inverse method to estimate during 1 year heat and water fluxes for the whole northwestern Mediterranean basin and at a fine‐scale resolution (i.e., hourly fluxes and 0.04° × 0.04° longitude, latitude) allowing to close the heat and freshwater budgets. The comparison of theses adjusted fluxes with fluxes estimated at the LION buoy from in situ meteo‐oceanic measurements shows a good correlation ( r2=0.96) and provides a validation of the parameterization used for the estimates of the turbulent air‐sea fluxes from the LION buoy (see Caniaux et al's Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…To document the chronology and hydrological properties of deep convection, we analyze LION buoy and mooring data. LION meteorological buoy (Caniaux et al, ) is located within the DWF area (42.102°N 4.703°E, Figure ). It provides all the near‐surface observable meteorological parameters and radiative fluxes (incoming longwave and shortwave radiation) since 2012.…”
Section: Model Data and Methodsmentioning
confidence: 99%
“…It provides all the near‐surface observable meteorological parameters and radiative fluxes (incoming longwave and shortwave radiation) since 2012. The data were validated following the procedure described by Caniaux et al (), and hourly turbulent fluxes (latent and sensible heat fluxes, and wind stress) were computed with the COARE3.0 flux algorithm (Fairall et al, ) for the period 1 August 2012 to 30 June 2013. Due to missing sequences of values and rejected data, the record of fluxes is limited to only 1808 hourly fluxes (21% of the 2012–2013 period).…”
Section: Model Data and Methodsmentioning
confidence: 99%
“…They showed that a one‐dimensional description of the vertical exchanges remains problematic because of the presence in the marine atmospheric boundary layer of organized structures such as two‐dimensional rolls favored by strong winds and surface heat fluxes. Caniaux et al () using measurements at the air sea interface and in the water column implemented an inverse method to estimate heat and water fluxes during 1 year for the NWM basin at a fine‐scale resolution. They compared air‐sea fluxes adjusted using observations, with some operational numerical weather prediction models (such as ARPEGE, NCEP, ERA‐Interim, ECMWF, and AROME) and concluded that these models were unable to retrieve the mean annual patterns and values of fluxes.…”
Section: Major Outcomesmentioning
confidence: 99%